In vivo protective effects of chlorogenic acid against triptolide-induced hepatotoxicity and its mechanism - Jun-Ming Wang; Rong-Xing Chen; Lu-Lu Zhang; Ning-Ning Ding; Chen Liu; Ying Cui; Yong-Xian Cheng (Taylor & Francis Group, 2018)
Context: Triptolide (TP) has outstanding biological activities, but it induces toxicities, particular hepatotoxicity, severely limiting its clinical application. Chlorogenic acid (CGA) has prominently medicinal and nutritional values. However, until now, it is not known whether CGA could mitigate TP-induced hepatotoxicity. Objective: This study explored the possible protection of CGA against TP-induced hepatotoxicity and its potential mechanisms, for the first time. Material and methods: KM mice were treated orally with TP at a single dose of 1 mg/kg at 4 h after being treated with CGA (10, 20 and 40 mg/kg) for seven continuous days. Blood samples were collected at 24 h after TP administration for measurement of serum biomarkers, and hepatic tissues for analysis of potential mechanisms. Results: TP treatment-induced acute hepatotoxicity manifested by the significant elevation in serum alanine transaminase (93.9 U/L), aspartate transaminase (185.8 U/L) and hepatic malondialdehyde (0.637 μmol/mg protein), and the remarkable reduction in hepatic glutathione (1.425 μg/mg protein), glutathione S-transferase, glutathione peroxidase, superoxide dismutase and catalase (91.7, 320.7, 360.6 and 140.7 U/mg protein, respectively). In contrast, pretreatment with CGA for 7 days effectively attenuated acute liver injury and oxidative stress caused by TP with each ED50 of 44.4, 57.1, 46.6, 22.2, 40.9, 58.1, 86.4 and 61.0 mg/kg, respectively. Furthermore, pretreatment with CGA promoted the accumulation of Nrf2 into the nucleus, and up-regulated mRNA expression of Nrf2-target downstream genes. Discussion and conclusions: Combined CGA medication may probably reduce the risk of TP poisoning, and in-depth mechanisms can be developed around the signal molecules of Nrf2.